Effect of the TRIMING Project on the Socioeconomic Characteristics of Rice Farmers in three selected locations along Kano River - Abdulwahab, F.S.; Abdullahi S.; Alhasan, A.; Aliyu, A.S.; Iliyasu, A.B. (Journal of Current Research and Studies, 2025)
The Transforming Irrigation Management in Nigeria (TRIMING) project was introduced to enhance agricultural productivity, particularly among rice farmers, through improved irrigation management. This study examines the effect of the TRIMING project on the socioeconomic characteristics of rice farmers in Kano State, Nigeria. A two-stage sampling technique was used to select 270 rice farmers (135 beneficiaries and 135 non-beneficiaries) for data collection. Descriptive statistics and regression analysis were employed to analyze the data. Findings indicate that the TRIMING project significantly improved farmers' income, access to credit, and adoption of modern farming techniques. However, challenges such as limited access to extension services and high input costs persist. The study recommends increased government support and farmer education to sustain the project’s benefits.